Transient myocardial ischaemia after acute myocardial infarction does not induce ventricular arrhythmias. Issue 4 (April 1993) - Currie, P; Saltissi, S
Abstract : OBJECTIVE–To see whether transient myocardial ischaemia on ambulatory monitoring after myocardial infarction is associated with ventricular arrhythmias. DESIGN–A prospective study. SETTING–The coronary care unit, general medical wards, and cardiorespiratory department of a major teaching hospital. PATIENTS–203 consecutive patients without specific exclusion criteria admitted with acute myocardial infarction. INTERVENTIONS–24 hour ambulatory electrocardiographic monitoring for ventricular arrhythmias and ST depression both early (mean 6.3 days after infarction, n = 201) and late (mean 38 days, n = 177). MAIN OUTCOME MEASURES–Episodes of myocardial ischaemia were identified during ambulatory monitoring by transient ST depression of > or = 1.0 mm lasting for > or = 30 s. Ventricular arrhythmias were single extrasystoles, couplets, or ventricular tachycardia. RESULTS–All ventricular arrhythmias were significantly more frequent in late than early monitoring. The arrhythmias included couplets (in 83/174 (48%) v 49/200 (25%) of patients, p = 0.0000028) and ventricular tachycardia (29/174 (17%) v 15/199 (8%), p = 0.0064). Patients with ST depression (29 early; 56 late), compared with those without ischaemia, did not experience a significant increase in single extrasystoles, couplets (31% v 23% early; 47% v 48% late), or ventricular tachycardia (3% v 8% early; 18% v 16% late). Even patients with frequent (> or = 3 episodes), and deep (> or = 1.5 mm) or prolonged (> or = 20 min) ST depression had no increase in arrhythmias. CONCLUSIONS–Ventricular arrhythmias after myocardial infarction are not associated with transient myocardial ischaemia during daily activities. This study does not support the belief that to abolish silent ischaemia would reduce the incidence of sudden death due to uncontrollable ventricular arrhythmias after myocardial infarction.